Serum Adiponectin and Resistin Levels in de Novo and Relapsed Acute Lymphoblastic Leukemia Children Patients - Hatim A El-Baz; Tamer E Mosa; Elham M Elabd; Amal Ramadan; Ahmed S Elharoun; Elsayed A Elmorsy; Manal I Fouda (Tehran University of Medical Sciences, 2013)
Background: Adipose tissue secretes a large number of adipocytokines such as leptin, resistin, and adiponectin. Many of these hormones and cytokines are altered in obese individuals and may lead to disruption of the normal balance between cell proliferation, differentiation, and apoptosis. The aim of our work was to investigate the disturbance of secretion of adiponectin and resistin in de novo and relapsed acute lymphoblastic leukemia (ALL) in Egyptian children and determine whether adiponectin and resistin are implicated in increased risk relapse compared to healthy individuals.Methods: Measurements of adiponectin and resistin were performed at diagnosis, in 32 patients with de novo ALL aged 3 to 18 years (mean 9.8 y) and 19 children with relapsed ALL aged 5 to 17 (mean 9.9 yr). 10 apparently healthy children with matched age and sex were used as controls.Results: Mean adiponectin levels were low (P < 0.05), whereas mean resistin levels were high (P<0.05) at diagnosis and relapsed ALL (compared to healthy controls). A significant decrease of adiponectin levels was observed in relapsed ALL compared to de novo ALL. In contrast resistin was significantly increased in relapsed ALL compared to de novo patients. Adiponectin in ALL subjects inversely correlated with resistin level (r = -0.51, P < 0.001).Conclusion: Low adiponectin and high resistin level at diagnosis suggest their implication in ALL pathogenesis and may serve as potential clinically significant diagnostic markers to detect leukemic relapse.